2007
DOI: 10.1038/sj.hdy.6801066
|View full text |Cite
|
Sign up to set email alerts
|

Transmission ratio distortion in Arabidopsis lyrata: effects of population divergence and the S-locus

Abstract: We investigated transmission ratio distortion within an Icelandic population of Arabidopsis lyrata using 16 molecular markers unlinked to the S-locus. Transmission ratio distortion was found more often than expected by chance at the gametic level, but not at the genotypic or zygotic level. The gametic effect may be due to meiotic drive or selection acting postmeiotically. At the gametic level, 10.9% of the tests were significant, which is substantially lower than earlier observed in an interpopulation cross (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…In Silene latifolia, a dioecious plant, the 3:1 sex ratio bias between females and males may be the result of pollen competition between X-bearing and Y-bearing pollen (Taylor and Ingvarsson, 2003). In Arabidopsis lyrata, several cases of segregation distortion have been reported, and most were due to gametic effects (Leppala et al, 2008). In addition, diversity at the self-incompatibility S locus in A. lyrata drives strong distortion between incompatible alleles.…”
Section: Discussionmentioning
confidence: 99%
“…In Silene latifolia, a dioecious plant, the 3:1 sex ratio bias between females and males may be the result of pollen competition between X-bearing and Y-bearing pollen (Taylor and Ingvarsson, 2003). In Arabidopsis lyrata, several cases of segregation distortion have been reported, and most were due to gametic effects (Leppala et al, 2008). In addition, diversity at the self-incompatibility S locus in A. lyrata drives strong distortion between incompatible alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Larraya et al (2001) also hypothesized that balancing selection acting on the recognition loci of P. ostreatus provides a possible explanation for the segregation distortion observed at the mat loci of this fungus. This is because balancing selection, which is thought to maintain the highly polymorphic multi-allelic nature of the recognition loci and the even distribution and long persistence of alleles in populations (Meyer and Thomsen, 2001), also results in the maintenance of potentially deleterious mutations in a population that would otherwise have been lost due to negative selection (Leppälä et al, 2008). Thus, balancing selection will prevent the loss of alleles associated with slow growth resulting in segregation distortion of these alleles.…”
Section: Genetic Determinants Of the Evolution Of The Recognition Locimentioning
confidence: 99%
“…The presence of alleles for slow growth at the het loci, which are known to encode genes involved in housekeeping and other functions (Saupe, 2000), would therefore influence the fitness of individuals negatively. In the case of the mat loci, balancing selection could also affect genes that play no apparent role in mating but that have become entrapped at the mat loci (e.g., Uyenoyama, 2005;Leppälä et al, 2008). This is especially true as some of them encode proteins vital for growth such as ketopantoate reductase involved in energy metabolism and that is encoded at the agaricomycetes mat-A locus (James et al, 2004;Niculita-Hirzel et al, 2008).…”
Section: Genetic Determinants Of the Evolution Of The Recognition Locimentioning
confidence: 99%
See 1 more Smart Citation
“…Dowd et al (2000) indeed found only 13 genes near the S locus in Petunia inflata. However, two studies have demonstrated the existence of transmission ratio distortion of some S alleles in A. lyrata (Bechsgaard et al 2004;Leppala et al 2008). The authors proposed that this could be indirect evidence of the existence of a sheltered load.…”
mentioning
confidence: 99%